Influence of ESG Ratings on Profitability Ratio in Company with ESG Values - Masarrah, Syalia; Suryaningrum, Diah Hari (PT. Riset Press International, 2025)
The research goal is analyze the influence of ESG ratings on financial ratios. Financial ratio studied is profitability, with ROA as an indicator, in companies listed with ESG values ​​on the Indonesia Stock Exchange. This study seeks to address the issue of how companies maintain their financial resilience and stability. This is based on the phenomenon of GHG emissions from research by the European Department of Communications in 2024. Quantitative methods were used to examine 13 samples consisting of 5 companies in the energy sector and 8 companies in the infrastructure sector from 2019-2023. The sample size was selected using a purposive sampling method. Data analysis techniques used were descriptive statistical analysis and regression analysis, processed using IBM SPSS version 26. Meanwhile, data tabulation was performed using Microsoft Excel. The results of this study indicate that ESG ratings have a significant positive effect on the profitability financial ratio with ROA as an indicator. This is supported by the robustness test results using the regression method with the addition of control variables, proving the model's robustness. Based on these results, the implications of this study are that it can serve as a reference for companies implementing ESG to improve their ROA, and for investors when selecting companies to invest.